2014
DOI: 10.1080/17441692.2014.979856
|View full text |Cite
|
Sign up to set email alerts
|

One for all: Workplace social context and drinking among railway workers in Ukraine

Abstract: Alcohol consumption is a leading cause of mortality and morbidity in countries of the former Soviet Union, but little is known about its social determinants. Recent research has suggested that workplace contexts may play a role. Using qualitative methods, we investigate the relationship between workplace social contexts and drinking in Ukraine. We conducted 24 individual semi-structured interviews and two focus group discussions in Lviv and Kharkiv, Ukraine, with male railway employees aged 18+ years. Data wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 47 publications
(58 reference statements)
0
6
0
Order By: Relevance
“…Consistent with other studies this study showed that the construction and performance of Russian masculine identity is entwined with heavy drinking [ 8 , 38 , 44 ] and that heavy drinking in all-male groups (especially with work colleagues and in young adulthood) was seen as routine, expected behaviour. All-male drinking occasions had a social function (particularly among young men) because they fostered male camaraderie and identity, and strong social and work bonds, similar to contemporary accounts of railway workers’ drinking in Ukraine [ 10 ], and to Scottish men’s accounts of drinking and friendship [ 65 ]. Increased social participation is likely to have various (potentially offsetting) influences on health behaviours [ 66 ], but in the context of Eastern Europe male sociability appears associated with higher levels of alcohol use [ 67 ] driven by the norms of masculine behaviour.…”
Section: Discussionmentioning
confidence: 91%
See 2 more Smart Citations
“…Consistent with other studies this study showed that the construction and performance of Russian masculine identity is entwined with heavy drinking [ 8 , 38 , 44 ] and that heavy drinking in all-male groups (especially with work colleagues and in young adulthood) was seen as routine, expected behaviour. All-male drinking occasions had a social function (particularly among young men) because they fostered male camaraderie and identity, and strong social and work bonds, similar to contemporary accounts of railway workers’ drinking in Ukraine [ 10 ], and to Scottish men’s accounts of drinking and friendship [ 65 ]. Increased social participation is likely to have various (potentially offsetting) influences on health behaviours [ 66 ], but in the context of Eastern Europe male sociability appears associated with higher levels of alcohol use [ 67 ] driven by the norms of masculine behaviour.…”
Section: Discussionmentioning
confidence: 91%
“…Previous qualitative studies have highlighted how Russian male heavy drinking is related to demonstrations of masculinity, and is more common in male-dominated environments such as blue-collar workplaces [ 8 , 10 , 11 ]. This is consistent with findings from quantitative surveys that hazardous drinking in Russia is more common among men with lower socio-economic status [ 12 16 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Contextual factors embedded in work environments may contribute to the inconsistency across the reviewed studies, because broad employment categories were often used or only selected occupations were included. Alcohol drinking aggregates in certain occupations through multiple pathways, such as socializing, the share of alcohol availability, and the level of alcohol management . Furthermore, criticism has been that the overpresentation of socioeconomically‐privileged workers in the long working hour group may cause bias, because long working hours may not necessarily be a stress to these workers and subsequently lead to drinking.…”
Section: Introductionmentioning
confidence: 99%
“…22-25 While producing invaluable evidence, leading studies in the field have tended to be epidemiological and quantitative. There are, however, a few noteworthy exceptions.…”
Section: Introductionmentioning
confidence: 99%